Individual stories sammeln als Porträt und Methodologie = Individual stories : collecting as portrait and methodology - Lo Pinto, Luca 1981-; Schafhausen, Nicolaus 1965-; Schmitz, Anne-Claire 1981- (Sternberg Press, 2015)
Photographs, books, and knickknacks: artists collect a variety of objects. While artists generate personal collections, which often address different formal, aesthetic, or conceptual concerns, it is difficult to separate this activity from their artistic practices. Over time, whether intended or not, such accumulations of items may become works of art. Individual Stories considers the collection as a portrait of its collector and also as an artistic method—as a process rather than an end result. The act of collecting is multifarious—it can be an expression of curiosity, a desire to transform things that have been discovered, or a systematic approach to certain objects in the world. This catalogue is a compilation of individual collections that could not be more different.